An Efficient Plant Regeneration and Transformation System of Ma Bamboo (Dendrocalamus latiflorus Munro) Started from Young Shoot as Explant - Ye, Shanwen; Cai, Changyang; Ren, Huibo; Wang, Wenjia; Xiang, Mengqi; Tang, Xiaoshan; Zhu, Caiping; Yin, Tengfei; Zhang, Li; Zhu, Qiang (Frontiers in Plant Science, 2017)
Genetic engineering technology has been successfully used in many plant species, but is limited in woody plants, especially in bamboos. Ma bamboo (Dendrocalamus latiflorus Munro) is one of the most important bamboo species in Asia, and its genetic improvement was largely restricted by the lack of an efficient regeneration and transformation method. Here we reported a plantlet regeneration and Agrobacterium-mediated transformation protocol by using Ma bamboo young shoots as explants. Under our optimized conditions, embryogenic calluses were successfully induced from the excised young shoots on callus induction medium (CIM) and rapidly grew on callus multiplication medium (CMM). Shoots and roots were regenerated on shoot induction medium (SIM) and root induction medium (RIM) respectively with high efficiency. An Agrobacterium-mediated genetic transformation protocol of Ma bamboo was established, verified by PCR and GUS staining. Furthermore, the maize Lc gene under the control of the ubiquitin promoter was successfully introduced into Ma bamboo genome and generated an anthocyanin over-accumulation phenotype. Our methods established here will facilitate the basic research as well as genetic breeding of this important bamboo species.